Pola Penginjilan Lintas Budaya oleh Tenaga Utusan Gereja (TUG) berdasarkan Kisah Para Rasul 8:26-40 di Gereja POUK Ichtus Bumi Dirgantara Permai Bekasi - Edu Arto Silalahi; Yaret Nesimnasi (Jurnal Arrabona, 2022)
The church exists because there is a mission. Therefore, the living church should remain focused on the mission of evangelism. Evangelism is a top priority that must be done by the church in a wide dimension, to the ends of the earth. In reality, there are many churches that are not active in the worldwide evangelistic missionary movement. Why? Is it because the church doesn't want to be involved in the mission or because the church doesn't know about missions? Evangelism must be an ongoing movement. Evangelism is carried out cross-culturally both within the country itself and abroad where neglected tribes (STA) are still found. In an effort to maximize cross-cultural evangelism, the church needs to hold congregational member development continuously. Coaching is intended to change and equalize perspectives or perspectives on cross-cultural evangelism missions. Based on observations and interviews conducted with several church missionaries (TUG) of the POUK Ichtus Bumi Dirgantara Permai Bekasi, it was found that the obstacles to cross-cultural evangelism were not primarily the ethnic groups to be served, but the readiness of the envoys who would serve cross-culturally. These obstacles are mainly related to language, culture and life values ​​that should be studied carefully before serving in these neglected tribes. By referring to the Bible, Acts 8:26-40, the principles and patterns of cross-cultural evangelism are found by studying the profile of Philip who preached the gospel across cultures. Key Words: Evangelism, Cross-cultural, messenger, church